3D Animation Design with the Islamic Theme "Birrul Walidain" Using the Pose-to-pose Method - Khoiriyah, Lailatul; Nurhidayah, Intan; Hadi, Muhammad Aulia Syamsul; Karami, Akhmad Fahmi; Nugroho, Fresy (Maliki Interdisciplinary Journal, 2024)
3D animated films are a genre that is very popular among various groups, from children to adults. The attractive visual appearance and simple story make it popular with many people. Animated films often present funny, historical and educational stories that contain moral messages, conveyed in a light way that is easy to understand. Therefore, animated films are often used as an educational tool, including to convey Islamic values. This research aims to educate and provide information regarding the obligation to help each other among fellow religious believers. In this research, a 3D animated film was made which shows that Muslims are obliged to help other people in need. This animation was made using Blender, open-source software which can be downloaded from the official website. The method used is the Pose-to-Pose method, which determines key poses in the movement so that animations are easier to create. Based on this background, the author designed a 3D animated film with the theme "Birrul Walidain." This film contains education and a moral message that invites the audience to understand that life will be more beautiful if parents love their children and children respect their parents. It is hoped that this animation will inspire other animation makers to convey moral messages through interesting and effective media.